Prevalence, Virulence Characterization, AMR Pattern and Genetic Relatedness of Vibrio parahaemolyticus Isolates From Retail Seafood of Kerala, India - Narayanan, Sreejith V.; Joseph, Toms C.; Peeralil, Shaheer; Mothadaka, Mukteswar P.; Lalitha, Kuttanappilly V. (Frontiers in Microbiology, 2020)
Vibrio parahaemolyticus, a halophilic bacterium often found in the marine or estuarine environment is a well-known enteropathogen responsible for foodborne outbreaks associated with seafood. The pathogenic strains of V. parahaemolyticus are marked by the presence of thermostable direct hemoylsin (tdh) and/or TDH related hemolysin (trh) genes. This study aimed to investigate the prevalence and characteristics of potentially pathogenic V. parahaemolyticus in selected retail markets of Cochin, Kerala, along the south-western coast of the Indian subcontinent. One hundred samples collected from 10 retail markets were analyzed for the presence of pathogenic V. parahaemolyticus. Out of the 721 presumptive isolates, 648 were confirmed as V. parahaemolyticus by toxR gene amplification, among which 29 were Kanagawa phenomenon (KP) positive. Among these potentially pathogenic isolates, 17 possessed the tdh gene whereas none had the trh gene. The faint amplification bands produced during the amplification of tdh gene from two isolates was confirmed by sequencing. Multiplex O serotyping identified O1 serotype as the most prevalent serotype among the 29 potentially pathogenic isolates. Further, studies on the pandemic nature of these isolates revealed that 14 of the 29 were positive for the PGS-PCR, whereas all the isolates were negative for GS-PCR and HU-α PCR. The antibiogram of the isolates revealed that three isolates had significant Multiple Antibiotic Resistance index of 0.2 or above. Pathogenic isolates resistant to second, third and fourth generation Cephalosporins were present in the seafood studied. The molecular fingerprinting studies using ERIC PCR and PFGE revealed that 3 of these isolates shared close genetic similarities with the clinical strains. The environmental and seafood isolates that produced faint amplification bands during the amplification of tdh gene suggests that the tdh gene often goes undetected in environmental isolates. The conventional methods used to identify the pathogenic V. parahaemolyticus would be good for clinical isolates, but a more elaborate method is recommended for the detection of tdh in environmental isolates. This is the first comprehensive study on pathogenic V. parahaemolyticus in Kerala, India and demonstrates for the first time, the isolation of potentially pathogenic V. parahaemolyticus, carrying tdh gene from seafood from retail markets in Kerala.